Circadian rhythms enable efficient resource selection in a human‐modified landscape. Issue 13 (21st June 2019) - Fischer, Manuela; Di Stefano, Julian; Gras, Pierre; Kramer‐Schadt, Stephanie; Sutherland, Duncan R.; Coulson, Graeme; Stillfried, Milena
Abstract: Animals access resources such as food and shelter, and acquiring these resources has varying risks and benefits, depending on the suitability of the landscape. Some animals change their patterns of resource selection in space and time to optimize the trade‐off between risks and benefits. We examine the circadian variation in resource selection of swamp wallabies ( Wallabia bicolor ) within a human‐modified landscape, an environment of varying suitability. We used GPS data from 48 swamp wallabies to compare the use of landscape features such as woodland and scrub, housing estates, farmland, coastal areas, wetlands, waterbodies, and roads to their availability using generalized linear mixed models. We investigated which features were selected by wallabies and determined whether the distance to different landscape features changed, depending on the time of the day. During the day, wallabies were more likely to be found within or near natural landscape features such as woodlands and scrub, wetlands, and coastal vegetation, while avoiding landscape features that may be perceived as more risky (roads, housing, waterbodies, and farmland), but those features were selected more at night. Finally, we mapped our results to predict habitat suitability for swamp wallabies in human‐modified landscapes. We showed that wallabies living in a human‐modified landscape selected different landscape features during day or night. Changing circadian patterns of resource selection might enhance the persistence of species in landscapes where resources are fragmented and disturbed. Abstract : We present how swamp wallabies access resources on a circadian in a human‐modified landscape, a landscape of varying suitability. We assessed the use of different landscape features to their availability by comparing 48 GPS tracked wallabies to correlated random walks. We determined whether resource selection of swamp wallabies varied during day and night, based on perceived risks (Photo credit: Cathy Cavallo).